The Association Between Diabetic Retinopathy and the Prevalence of Age-Related Macular Degeneration—The Kailuan Eye Study - Yongpeng, Zhang; Yaxing, Wang; Jinqiong, Zhou; Qian, Wang; Yanni, Yan; Xuan, Yang; Jingyan, Yang; Wenjia, Zhou; Ping, Wang; Chang, Shen; Ming, Yang; Yanan, Luan; et al. (Frontiers in Public Health, 2022)
Objective: To investigate the prevalence of age-related macular degeneration (AMD) in diabetes (DM) patients with diabetic retinopathy (DR), and to analyze whether DR is a risk factor for AMD. Methods: A population-based epidemiological study was conducted. In Kailuan Eye Study, 14440 people were included, of whom 1618 were type 2 DM aged over 50, and 409 were DM with DR. We analyzed whether there were differences in the prevalence of AMD between DM with DR and DM without DR, and conducted hierarchical statistical analysis according to different stages of DR. By variable regression analysis, we explored whether DR constituted a risk factor for AMD. Results: In DM population, the prevalence of wet AMD in DM with DR and DM without DR were 0.3% and 0.2% respectively, with no significant difference (P=0.607). The prevalence of dry AMD in DM with DR and DM without DR were 20.8% and 16.0% respectively with significant difference. In the subgroup analysis of dry AMD, the prevalence of early, middle and late dry AMD in DM with DR were 14.4%, 5.9% and 0.5% respectively. In DM without DR, the prevalence of early, middle and late dry AMD were 10.5%, 4.8% and 0.7% respectively (P=0.031). In the subgroup analysis of DR staging, statistical analysis cannot be carried out because the patient number of PDR is limited. In the variable regression analysis of risk factors of dry AMD, after adjusted for age, gender, body mass index, hypertension and dyslipidemia, DR constituted the risk factors of dry AMD. Conclusion: In this study, DM itself does not constitute a risk factor for AMD, but the prevalence of wet AMD and dry AMD in DM patients with DR is higher than that in DM patients without DR (among which dry AMD is statistically significant). Multivariate regressive analysis confirmed that DR was an independent risk factor for dry AMD. Reasonable control of DM and slowing down the occurrence and development of DR may effectively reduce the prevalence of AMD in DM population.